Gembala Sebagai Guru Dalam Pembinaan Warga Gereja - Aan Aan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The presence of the Church in the midst of today's globalized world has a very heavy task, because of that the church needs to teach each of its members so that they are able to make good and useful contributions in the midst of this world. A pastor needs to help his members develop a mature, firm, and Christ-like character through the formation of church members. The purpose of writing is to describe the role of the pastor as a teacher who teaches and educates the congregation in fostering church members. The methodology used in this study is a descriptive qualitative research methodology with a literature study approach. The results of the research show that the shepherds are still ignorant of their pedagogical calling. For this reason, pastors need to take a role and optimize teaching and education through worship, through Bible understanding activities and also through small group activities. If the pastor carries out his function as a teacher who teaches and educates, then this will have a positive impact on the spiritual growth of the congregation and even be able to contribute to preventing the negative impacts of the world today